Force of summation - Gregorics, Tibor (Teaching Mathematics and Computer Science, 2014)
Programming theorems are important tools of programming methodology. By using analogous programming techniques, the solutions of different tasks can be created easily and fast based on programming theorems. Perhaps the summation is the simplest programming theorem that is widely-known among the programmers but once and for all the most various tasks can be solved by this theorem. The aim of the present paper is to investigate the summation programming theorem. Several different abstract levels of this theorem will be defined and the problem types that can be solved based on summation are going to be described. We will underline those points of a programming theorem that make a theorem general and that are not defined in advance, just later during its application, when the solution of a problem is derived from the theorem.